Sally Harper, Music in Welsh Culture Before 1650: A Study of the Principal Sources (2007) - Buckley, Ann (Journal of the Society for Musicology in Ireland, 2008)
A review of Sally Harper, Music in Welsh Culture Before 1650: A Study of the Principal Sources (Aldershot: Ashgate, 2007), ISBN 978-0-7546-5263-2, xx + 462pp, 99.95/£60.